Authentic gender development in non-binary children - Salinas-Quiroz, Fernando; Sweder, Noah (Frontiers in Sociology, 2023)
At present, the conceptualization of gender as a spectrum as well as nonbinary identities have become increasingly visible and embraced. We are using nonbinary as an umbrella term that refers to individuals who self-identify as a gender outside the gender binary, and/or who do not identify as always and completely being just a man or a woman. Our goal is to begin to create a framework for understanding gender development in nonbinary children ages 0 to 8, since previous models have operated on cissupremacist assumptions, not applicable to nonbinary people. As there is virtually no empirical data on the subject, we conducted a thorough literature review of current gender development theories and used our positionality as nonbinary researchers to postulate two minimum criteria for nonbinary gender identification: that a child learns about the existence of nonbinary identities, and that they do not identify with the definitions they have been taught of what a boy or girl is. Children can learn about nonbinary identities through media and knowledgeable community members and can develop “gender traits” authentically and come to identify as nonbinary through biological predispositions, parental support, modeling, and being in peer groups that are supportive of identity exploration. Yet, children are not simply a product of their nature and nurture, as evidence has shown that humans are active agents in their gender development from a young age.